Features of pregnancy after simultaneous pancreas-kidney transplantation in patient with type 1 diabetes mellitus. Case report - Madina I. Yevloyeva; Darya U. Savitskaya; Anastasia S. Severina; Minara S. Shamkhalova; Natalia P. Trubitsyna; Marina V. Shestakova (Терапевтический архив)
Simultaneous pancreas and kidney transplantation the best way to restore normoglycemia and renal function in patients with type 1 diabetes mellitus and terminal chronic kidney disease. Pregnant patients after simultaneous pancreas and kidney transplantation are a high-risk group for adverse events/loss of both fetal and grafts. These risks are significantly reduced with pregnancy planning, regular monitoring of the woman and fetus with timely correction of immunosuppressive therapy, maintenance of target blood pressure and glycemia, selection of optimal timing and method of delivery. The presented clinical case demonstrates the need for an comprehensive multidisciplinary approach to the management of pregnancy and delivery with minimization of potential risks for mother and child.